Un Estado al alcance de todos: mejorando la experiencia de cobro de los usuarios de Pensión 65 - Mori Matienzo, Sandra Victoria (2024)
According to the User Perception Surveys of the Pension 65 program, carried out between 2018 and 2022, it was identified that, although many beneficiaries perceive an improvement in their well-being, there is significant dissatisfaction in relation to the pension collection process. grant. Approximately 37% of users surveyed reported difficulties accessing payment points. This is worrying since it implies that more than a third of users do not have adequate collection experience, even more so if we take care that they are older adults and in extreme poverty. Along these lines, this work starts from the identification of this problem and seeks to find innovative solutions, especially to generate well-being in users and facilitate access to the collection of the subsidy. For this reason, a process of analysis and investigation was carried out on the main causes that generate dissatisfaction in users, identifying the following: difficulty in traveling to collection points, high opportunity cost and lack of knowledge of payment points. and use of digital banking. Then, the causes were validated by the users themselves and it was possible to identify that the cause with the greatest impact on the problem is the difficulty in traveling to the collection points. Now, the question is how can we improve the movement to the collection points, by users, to optimize the experience of collecting the subsidy? To answer this question, comparative experiences in other countries were analyzed and the opinions of experts in the field were obtained. Three possible solution prototypes were identified to be validated by users and experts, with the chosen prototype being the concentrator switch to diversify the payment points of Pensión 65, based on the Ecuadorian experience. After the suggestion and analysis with experts and Midis officials, the innovation called "Scan Pension 65" is presented wich consists of local businesses made up of small Foncodes producers can use a card reader or PoS, through of the use of the Internet, and thus, act as banking agents for the users.